Relasi Interpersonal dan Motivasi Diri dalam Pembentukan Kemandirian Santri Tunanetra - Shidqi, Muhammad; Nuraeni, Yeni (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study aims to analyze the relationship between interpersonal communication and self-motivation in supporting the independence of blind students at the Bina Insan Mulia Cianjur (BIMCI) Islamic Boarding School. This research focuses on how communication interactions between teachers, administrators, and students can help students with blind disabilities develop independence in everyday life. Using a descriptive qualitative approach, data were collected through in-depth interviews, direct observation, and documentation. The results showed that harmonious interpersonal relationships, based on the Fundamental Interpersonal Relations Orientation (FIRO) theory, which includes dimensions of inclusion, control, and compassion, are able to create empowering interactions. Self-motivation analyzed through Maslow's Hierarchy of Needs is also a key element in encouraging students to achieve self-actualization, which is supported by the fulfillment of basic needs such as security and acceptance. Open communication patterns, attention to individual needs, and the presence of teachers as companions make a significant contribution in increasing the confidence and independence of blind students. This research provides important implications for the need for inclusion-based communication training for teachers as well as the development of pesantren policies that support the sustainability of santri independence. The results of this study can enrich the study of communication science by presenting a new perspective on the application of FIRO theory and Maslow's Hierarchy of Needs in the context of inclusive community-based education.